2005
DOI: 10.1042/bj20050341
|View full text |Cite
|
Sign up to set email alerts
|

Post-translationally modified residues of native human osteopontin are located in clusters: identification of 36 phosphorylation and five O-glycosylation sites and their biological implications

Abstract: OPN (osteopontin) is an integrin-binding highly phosphorylated glycoprotein, recognized as a key molecule in a multitude of biological processes such as bone mineralization, cancer metastasis, cell-mediated immune response, inflammation and cell survival. A significant regulation of OPN function is mediated through PTM (post-translational modification). Using a combination of Edman degradation and MS analyses, we have characterized the complete phosphorylation and glycosylation pattern of native human OPN. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
208
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(220 citation statements)
references
References 47 publications
10
208
0
Order By: Relevance
“…Other studies have identified several phospho-Thrs in the SIBLINGs, with phosphorylation that is not governed by FAM20C (3,28,39). We confirmed the existence of some of these phospho-Thrs in the Fam20C-KO mice.…”
Section: Discussionsupporting
confidence: 77%
“…Other studies have identified several phospho-Thrs in the SIBLINGs, with phosphorylation that is not governed by FAM20C (3,28,39). We confirmed the existence of some of these phospho-Thrs in the Fam20C-KO mice.…”
Section: Discussionsupporting
confidence: 77%
“…For example, both bovine and human milk OPN have a large number of phosphorylated serine residues (28 and 32 respectively, mostly in motifs implicating casein kinase 2). These are located in clusters of 3-5 sites and these sites are absent from the RGD region as well as from the glycosylated region (Christensen et al, 2005;. In contrast, rat bone OPN (at least as isolated) contains only 10-11 phosphorylated residues (Keykhosravani et al, 2005).…”
Section: Post-translational Modifications (Ptm)mentioning
confidence: 99%
“…This OPN is phosphorylated at a few randomly located serine/threnine sites (out of some 30 potential sites) and presumably behaves as un-phosphorylated OPN (Christensen et al, 2005). OPN -/-mice were divided into 3 groups: (A) control group, (B) CRS group injected with PBS (C) CRS group injected with OPN in PBS.…”
Section: Administration Of Purified Opnmentioning
confidence: 99%
“…In OPN, tyrosine sulfation has been linked to tissue mineralization (Nagata et al 1989), and has been found in OPN isolated from rat bone (Keykhosravani et al 2005), mouse osteoblasts (Ecarot-Charrier et al 1989) and also from human urine (Christensen et al 2008), but not in human milk OPN (Christensen et al 2005). To our knowledge, there is at present no literature regarding the role of OPN sulfation on malignant properties of cancer cells.…”
Section: Post-translational Modifications Of Opnmentioning
confidence: 99%